Hydrogenation of succinic acid over supported rhenium catalysts prepared by the microwave-assisted thermolytic method1. Issue 4 (24th April 2015) - Di, Xin; Shao, Zhengfeng; Li, Chuang; Li, Wenzhen; Liang, Changhai
<x xml:space="preserve">Abstract</x> The Re/C catalysts prepared by the microwave-assisted thermolytic method exhibited good catalytic activity in the aqueous phase hydrogenation of succinic acid.